Talk like (wo)man analyzing Donald Trump's tweets and selected campaign speeches - Calvo, Esther Mary L.; Skripkina, Anastasiya (2018)
There is no denying that Donald Trump's speaking style is entertaining but what about his linguistic style? There is a plethora of studies about gender differences in language used by politicians but only few have used tweets for analysis. Unlike traditional methods, big data offers new possibilities of mining large-scale material for research. In this contribution, we make use of web scraping to collect the tweets (N=3,239) by Donald Trump prior to his election as president. To determine his linguistic style, we devised our own dictionary that contained both feminine and linguistics markers. The code for sentiment analysis was tweaked to yield a femininity score. Our analysis of his tweets tells us that indeed Trump has a natural feminine linguistic style. However, our findings from our analysis of some of his campaign speeches suggest otherwise.
Keywords: Speeches, addresses, etc